2017
DOI: 10.1007/s10441-017-9311-x
|View full text |Cite
|
Sign up to set email alerts
|

What do Biologists Make of the Species Problem?

Abstract: The concept of species is one of the core concepts in biology and one of the cornerstones of evolutionary biology, yet it is rife with conceptual problems. Philosophers of biology have been discussing the concept of species for decades, and in doing so they sometimes appeal to the views of biologists. However, their statements as to what biologists think are seldom supported by empirical data. In order to investigate what biologists actually think about the key issues related to the problem of species, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…It has long been common for papers about the species concept to start by pointing out how much has been written about the species problem, how vexing a problem it is, and how unlikely it is that biologists will ever agree about the definition of species. This was confirmed by a recent survey among biologists by Pušić et al (2017), which revealed great diversity in the preferred species concept of biologists. At the same time, many recent systematic studies suggest-often in passing-that biologists have reached agreement about what species are, namely, independently evolving lineages (Carstens et al 2013).…”
Section: Introductionsupporting
confidence: 60%
“…It has long been common for papers about the species concept to start by pointing out how much has been written about the species problem, how vexing a problem it is, and how unlikely it is that biologists will ever agree about the definition of species. This was confirmed by a recent survey among biologists by Pušić et al (2017), which revealed great diversity in the preferred species concept of biologists. At the same time, many recent systematic studies suggest-often in passing-that biologists have reached agreement about what species are, namely, independently evolving lineages (Carstens et al 2013).…”
Section: Introductionsupporting
confidence: 60%
“…People, and especially children, intuitively treat species taxa as categories made up of members, which share common, essential, observable, or not, characteristics and properties, and each of these categories is given a unique name (Dawkins, 2009;Hey, 2001;Shtulman, 2006). Also, biologists consider species taxa to be categories (Brigandt, 2009) and special natural kinds (Reydon, 2005) from the time of Aristotle (Hull, 1976) and continue to treat them in the same way even today (Pušic et al, 2017).…”
Section: Classes and Individualsmentioning
confidence: 99%
“…Brigandt claims that "most biologists and philosophers favor the idea that species are individuals rather than natural kinds" (2009,(77)(78). In contrast, a recent survey of the opinions of 193 biologists from over 150 biology departments at universities in the United States and the European Union (Pušić, Franjević, and Gregorić 2017) found that, among biologists themselves, the position of individualism is "utterly marginal," only 2.94%. I agree with those like Okasha (2002, 193-94) who think that this individualism is a red herring to the essentialism issue (Devitt 2008, 348).…”
mentioning
confidence: 91%